Inflammatory myofibroblastic tumour masquerading as acute appendicitis in a child: case report - Waheed, Muhammad Rehman; Mahwish Noor-Ul-Haq; Syed Salman Hussain Zaidi; Batool Fatima; Zuha Zafar; Muhammad Azam (Journal of the Pakistan Medical Association, 2026)
Inflammatory myofibroblastic tumour (IMT) is an uncommon and enigmatic neoplasm that can imitate a range of other medical conditions, frequently making it difficult to reach an accurate diagnosis. It primarily affects children, though there is a shortage of documented cases in the medical literature. The lungs are the most common location for this tumour to develop and intra-abdominal lesions are rare. Tumours arising from the small intestine and mesentery are exceptionally uncommon. This report highlights a rare case involving a 10-year-old child who presented to the emergency department exhibiting signs and imaging features that closely resembled acute appendicitis. However, surgical exploration revealed acutely inflamed appendix attached to a mass originating from the ileal wall, six feet proximal to the ileocecal junction, covered by necrotic omentum and another mass in the ileal mesentery just proximal to the ileocaecal junction. The child underwent surgical removal of the appendix along with both the abdominal masses. The excised tissues were analysed through histopathology, confirming the diagnosis of an inflammatory myofibroblastic tumour. The post-operative period was uneventful, and follow-up evaluations revealed no evidence of the recurrence of the tumour. Key words: Inflammatory myofibroblastic tumour, Appendicitis, Mesentery.